2018
DOI: 10.1111/jog.13671
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome of vaginal delivery with epidural analgesia initiated at the early or late phase of labor period: A retrospective cohort study in the Japanese population

Abstract: Most perinatal outcomes between the early and late phases of initiated epidural analgesia were not markedly different in our Japanese population, even when using a new definition of labor phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
2
5
1
Order By: Relevance
“…Although the majority of these studies were conducted in nulliparous spontaneous labor, the results of our study for the elective induction of labor in multiparous women appear to be in concordance regarding the effect on labor duration. In nulliparous women, the durations of labor with early and late neuraxial analgesia initiation were comparable 6–9,11 . Our study's findings are in line with these previous findings.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Although the majority of these studies were conducted in nulliparous spontaneous labor, the results of our study for the elective induction of labor in multiparous women appear to be in concordance regarding the effect on labor duration. In nulliparous women, the durations of labor with early and late neuraxial analgesia initiation were comparable 6–9,11 . Our study's findings are in line with these previous findings.…”
Section: Discussionsupporting
confidence: 91%
“…The only previous study that assessed the effects of the timing of analgesia initiation on multiparous women with spontaneous labor was conducted at a Japanese institution by Shiro et al 6 Similar to our study, the authors reported no statistically significant difference between the early and late groups in the first stage of labor 6 . However, the labor durations in the present study were shorter than those reported by Shiro et al (468 min in the early group and 372 min in the late group) 6 . We speculate that our active management of labor with oxytocin and the artificial rupture of the membrane could have contributed to the shorter duration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations